2022
DOI: 10.3389/fpubh.2022.985834
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of ensartinib, crizotinib, ceritinib, alectinib, brigatinib and lorlatinib in patients with anaplastic lymphoma kinase-positive non-small cell lung cancer in China

Abstract: ObjectiveSix anaplastic lymphoma kinase-tyrosine kinase inhibitors (ALK-TKIs), including one domestic (ensartinib) and five imported ALK-TKIs (crizotinib, ceritinib, alectinib, brigatinib, and lorlatinib), have been recommended as first-line treatments for advanced ALK-positive NSCLC in China. This study sought to examine the cost-effectiveness of these six novel therapies in Chinese patients.Material and methodsWe constructed a Markov model to compare the cost-effectiveness of the six ALK-TKIs as a first-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our study in combination with previous researches on costeffectiveness of cancer treatment (31,59,60), emphasizes the urgency to explore alternative pricing strategies due to the high costs associated with cancer agents. Value-based pricing (61), indication-specific pricing (62), or a subscription model ( 63) could be potential options to explore.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our study in combination with previous researches on costeffectiveness of cancer treatment (31,59,60), emphasizes the urgency to explore alternative pricing strategies due to the high costs associated with cancer agents. Value-based pricing (61), indication-specific pricing (62), or a subscription model ( 63) could be potential options to explore.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies evaluated the economic value of regimen regarding brigatinib for individuals who have ALK-positive NSCLC (29)(30)(31). The incremental cost-effectiveness ratio for these studies varies, for example, Cranmer et al (29) both applied clinical data from the ALTA-1 L and ALEX trials to assess brigatinib from a United States perspective, which demonstrated that brigatinib provided better results than crizotinib, resulting in an increase of 0.97 quality-adjusted life-years (QALYs).…”
Section: Introductionmentioning
confidence: 99%
“…19 China’s clinical testing and management costs referred to the research by Zhu et al . 20 The costs of AEs for CAR-T referred to the study by Luo et al 21 and were converted based on incidence. 7 Follow-up and physical examination data were collected after expert consultation.…”
Section: Methodsmentioning
confidence: 99%
“…18 The winning bid prices in each province in 2021 were queried on 'Yaozhi.com' to obtain the cost of the remaining pretreatment drugs. 19 China's clinical testing and management costs referred to the research by Zhu et al 20 The costs of AEs for CAR-T referred to the study by Luo et al 21 and were converted based on incidence. 7 Follow-up and physical examination data were collected after expert consultation.…”
Section: Model Inputmentioning
confidence: 99%